Modulation of the autonomic nervous system by one session of spinal low-level laser therapy in patients with chronic colonic motility dysfunction - Ali, M. Khawar; Saha, Shrayasee; Milkova, Natalija; Liu, Lijun; Sharma, Kartik; Huizinga, Jan D.; Chen, Ji-Hong (Frontiers in Neuroscience, 2022)
Patients with a defecation disorder may not evoke a normal defecation reflex executed by the spinal autonomic nervous system. Various forms of lumbar and sacral neuromodulation have shown positive results. Here we evaluate the effects of a single session of sacral low-level laser therapy (LLLT) on the lumbar and sacral spine in 41 patients with chronic gastrointestinal motor dysfunction. The LLLT protocol used red LED light at a wavelength of 660 nm for 10 minutes and infrared LED light at a wavelength of 840 nm for 10 minutes, followed by infrared laser light at a wavelength of 825 nm for 20 minutes. Effects on the ANS were assessed by measuring heart rate variability (HRV) changes. Respiratory Sinus Arrhythmia (RSA) and Root Mean Square for Successive Differences (RMSSD) were used to quantify parasympathetic reactivity; the Baevsky’s Stress Index (SI) reflected sympathetic reactivity while the ratios SI/RSA and SI/RMSSD were used to represent shifts in autonomic dominance. The results indicate that lumbar and sacral neuromodulation using LLLT using light arrays reduced, whereas the laser probe significantly increased parasympathetic reactivity. The light arrays increased whereas the laser probe significantly decreased sympathetic reactivity (SI), the entire protocol shifted the autonomic balance towards the parasympathetic nervous system. The comparison of actual versus sham neuromodulation proved that the change in HRV parameters was due to actual light stimulation and not due to touching of the arrays and probe to the skin. In conclusion, a single session of LLLT markedly affects autonomic nervous activity reflected in changes in HRV. These results warrant a study into the effects of LLLT on restoring autonomic dysfunction in chronic refractory colonic motility disorders and relieve of symptoms.